Reducing Fear of Missing Out (FoMO) Through Experiential Learning: A Quasi-Experimental Study in Vocational High Schools - Awalya Siska Pratiwi; Septia Rahmawati (AL-ISHLAH: Jurnal Pendidikan, 2025)
The rise of digital technology has contributed to increased Fear of Missing Out (FoMO) among adolescents, which negatively affects their emotional well-being and academic engagement. This study aimed to examine the effectiveness of Experiential Learning (EL) in reducing FoMO among vocational high school students. A quasi-experimental, one-group pretest-posttest design was used with 15 purposively selected 11th-grade students from SMK Nasional Malang who exhibited moderate to high FoMO scores. The intervention was based on Kolb’s experiential learning model and included role-playing, group discussions, and reflective activities. FoMO levels were assessed using a validated 10-item Likert scale adapted from Przybylski et al. (2013). Data were analyzed using the Wilcoxon Signed Rank Test. Findings showed a significant reduction in FoMO scores after the intervention (Z = -3.415, p = 0.001), with most participants moving from high to medium or low FoMO categories. Students also reported improved emotion regulation and time management. The experiential activities promoted active engagement, self-awareness, and practical coping strategies in managing digital pressure. The results support the use of experiential learning to reduce FoMO by enhancing emotional resilience and fostering healthier social interactions. Although limited by sample size and lack of a control group, the study provides promising evidence for integrating experiential methods into school-based guidance and counseling programs. Future research should employ randomized controlled trials to strengthen causal claims and explore long-term effects.